2020
DOI: 10.1038/s41419-020-02826-x
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PTPRM predicts poor prognosis and promotes tumor growth and lymph node metastasis in cervical cancer

Abstract: The prognosis for cervical cancer (CCa) patients with lymph node metastasis (LNM) is dismal. Elucidation of the molecular mechanisms underlying LNM may provide clinical therapeutic strategies for CCa patients with LNM. However, the precise mechanism of LNM in CCa remains unclear. Herein, we demonstrated that protein tyrosine phosphatase receptor type M (PTPRM), identified from TCGA dataset, was markedly upregulated in CCa with LNM and correlated with LNM. Moreover, PTPRM was an independent prognostic factor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…These findings indicate that the EMT phenotypes are context dependent [ 39 ] and CCa cells may not go through a full EMT, but rather adopt some qualities of mesenchymal cells and keep some epithelial characteristics during LN metastasis. Furthermore, the EMT phenotype often accompanied with increased lymphangiogenesis [ 40 , 41 ]. We observed that LNMAS exerted an inhibitory effect on lymphangiogenesis in vitro and in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the EMT phenotypes are context dependent [ 39 ] and CCa cells may not go through a full EMT, but rather adopt some qualities of mesenchymal cells and keep some epithelial characteristics during LN metastasis. Furthermore, the EMT phenotype often accompanied with increased lymphangiogenesis [ 40 , 41 ]. We observed that LNMAS exerted an inhibitory effect on lymphangiogenesis in vitro and in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The process involves several steps, including tumour secretion of lymphangiogenic factors [ 27 29 ], tumour lymphangiogenesis [ 28 ], lymph node lymphangiogenesis [ 30 ], and lymphatic vessel activation of metastatic tumour cells [ 31 ]. For example, PTPRM upregulation is relevant to LNM of CCa through VEGF-C-dependent lymphangiogenesis and Src-AKT signalling pathway-mediated EMT [ 32 ]. RACK1 promotes the invasive activities and LNM of CCa via galectin 1 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid rafts have been reported to be essential platforms for signaling regulation [ 19 ]. Thus, for a detailed mechanistic study, we first chose to clarify whether various signaling pathways, mTOR, ROCK, PI3K/AKT, and c-Src, which have been found to be related to cervical cancer tumorigenesis or progression [ 20 22 ], were involved. We intended to explore the upstream signaling pathway in regulating p-FAK.…”
Section: Resultsmentioning
confidence: 99%